2011
DOI: 10.2169/internalmedicine.50.4968
|View full text |Cite
|
Sign up to set email alerts
|

Feminizing Adrenocortical Carcinoma with Selective Suppression of Follicle-Stimulating Hormone Secretion and Disorganized Steroidogenesis: A Case Report and Literature Review

Abstract: We report a 61-year-old male with gynecomastia, poor libido and erectile dysfunction. Endocrinological studies showed high levels of estradiol and dehydroepiandrosterone sulfate. Although luteinizing hormone (LH) level was within the normal limit, the concentration of follicle-stimulating hormone (FSH) was under the normal limit. Delayed response of LH and poor response of FSH to gonadotropin-releasing hormone administration were detected. Magnetic resonance imaging of the abdomen revealed a left adrenal tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Feminizing adrenal tumors (FAT) are defined as adrenal neoplasms with estrogens (estrone and estradiol) overproduction with or without other adrenal hormones. [ 5 7 10 ] These exceedingly rare tumors are deemed to have a dire prognosis. [ 1 ] They are mainly observed in men or in children, and are exceptional in premenopausal and menopausal women.…”
Section: Efinition P Revalence mentioning
confidence: 99%
See 1 more Smart Citation
“…Feminizing adrenal tumors (FAT) are defined as adrenal neoplasms with estrogens (estrone and estradiol) overproduction with or without other adrenal hormones. [ 5 7 10 ] These exceedingly rare tumors are deemed to have a dire prognosis. [ 1 ] They are mainly observed in men or in children, and are exceptional in premenopausal and menopausal women.…”
Section: Efinition P Revalence mentioning
confidence: 99%
“…The last condition is very rare and the prognosis is deemed to be the worst. In literature only single cases have been reported in adults[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 19 21 22 23 24 25 25 ] and in pediatric population. [ 19 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 ] The largest published series does not exceed two[ 7 25 ] and three cases.…”
Section: Introductionmentioning
confidence: 99%
“…[15] 21 OHase, 3 beta- ol-deshydrogenase, and 11beta OHase-acquired deficits are responsible of an increase in some precursors such as androstenedione, 17OHP, and DHEA S that are converted to estrogens via an increase in aromatase activity. [16] As a consequence of estradiol excess, there is also an inhibition of pituitary function[17] especially for FSH. [6716] Gonadotropins inhibition may also be increased by inhibin production by the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown aromatase overexpression at the mRNA and protein levels in estrogen-secreting ACCs. [3][4][5][6] This may contribute to ectopic estrogen production in ACCs. However, performing detailed analyses of the steroidogenesis pathway by immunohistochemical analysis is difficult due to its low sensitivity and tumor heterogeneity.…”
Section: Introductionmentioning
confidence: 99%